Large-area Fe-C eutectic fixed-points for radiation and contact thermometry - Can, Mehtap; Gozonunde, Can; Arifovic, Narcisa; Yildiz, Fikret; Nasibov, Humbat (Iop Publishing Ltd, 2023)
High-quality metal (carbide)-carbon eutectic materials based on high-temperature fixed points (HTFPs) are widely used in radiometry and thermometry as reference standards. HTFPs on the base of iron-carbon (Fe-C) binary eutectic alloys, with a nominal melting temperature of about 1154 & DEG;C (just above the copper freezing point of 1084.62 & DEG;C), are one of the promising candidates among the eutectic materials. To establish new HTFPs as reference metrological tools for high-temperature thermometry, their performance should be thoroughly investigated regarding reproducibility and stability. In this work, two large-area (8 mm aperture, 107 mm cavity/thermowell length) Fe-C fixed-point cells were constructed and studied in detail using a radiation thermometer and two different thermocouples (TCs). Three different furnaces were used to explore the thermal behaviors of the cells at various furnace gradients and furnace offsets. The melting temperature at the inflections point of the melting curves of the cells studied across extensive measurement campaigns demonstrated good performance with repeatability of less than 9 mK (assessed from four successive runs) and reproducibility-less than 100 mK (at different furnaces and furnace offsets). The melting temperature agreement between both cells in the same experimental conditions was better than 30 mK. In addition, the equivalence of the developed large-area cells and a small-area radiometric cell (3 mm cavity aperture, and 35 mm cavity length) were comparatively examined in the same experimental conditions. The coherence of the obtained results for the melting temperature of large-area Fe-C cells indicates the feasibility of using large-volume cells for precise calibration of both radiation thermometers and TCs.
Keywords: iron-carbon eutectic; metal-carbon fixed-point; thermocouple; Fe-C; high-temperature cell